Interpersonal Communication for Conflict Management of Slander in Long Distance Relationship (LDR) - Rizky Johanuari Putri; Agus Naryoso, S.Sos, M.Si (Interaksi Online, 2016)
A relationship requires the existence of honesty, opennes, trust and time to be together. But in long distance relationship, sometimes those needs neglected because of they can’t do face to face communication everyday and it causes slanders in those couple. Therefore the aim of this research is to know the interpersonal communication for conflict management of slander in long distance relationship. The theory that used in this research is the Triangular Theory of Love, Self Disclosure Theory, and Conflict Management with descriptive qualitative type of research and phenomenological approach which define standpoint informant who has experience of slander during the dating. Research result that found from couple who has experience of slander is they talked about unimportant and important topic as a daily sharing. They do routine communication to show their intimacy, caring and sense of belonging each other. A meeting used as a time to share a longing of each other and talk a lot of things can warm up and motivating relationship. Therefor they can’t meet in everyday life, there is still suspicious feeling that trigger by odd attitude like takes a long time when picking up the phone, give the convoluted answer , and often permit to go with the opposite sex. This attitude make slanders more obvious, and infidelity is the most frequently slander that showed up. This slander takes a long time when each other can’t open to each other. Conflict resolution that effetive to long distance relationship couple is made through electronical mediated communication by telephone and chatting. Face to face communication isn’t an right way to cope conflict because it can’t be done directly and make conflict takes a long time to coped. Long distance relationship couple apologize and make promise to convince each other about wouldn’t do any event that trigger slanders in the future. Self disclosure in couple can make the resolution easier because each other knows what other needs.